Effect of Phosphorus And Sulphur on Yield of Brri Dhan 57 (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted during the period from July, 2011 to December, 2011 to on the performance study of rice regarding to growth, yield and yield contributing characters of rice BRRI dhan 57 under the AEZ-28. The two factors experiment consists with four levels of Phosphorus (P) viz. P0: without Phosphorus (control), P1: 20 kg ha1, P2: 40 kg ha1 and P3: 60 kg ha1 and four levels of Sulphur viz. S0: without Sulphur (control), S1: 10 kg ha1, S2: 20 kg ha1 and S3: 30 kg ha1. The result obtained from the study, it was found that all the traits were statistically significant due to Phosphorus whereas 40 kg P ha1 recorded the tallest plant (109.70 cm) at harvest and maximum tillers hill1 (17.58) at 85 DAT. Phosphorus @ 40 kg ha1 also recorded the greater results on effective tillers hill1 (13.67), panicle length (22.04 cm), filled grains panicle1 (138.60), 1000-grain weight (30.75 g), weight of grain, straw and biological yield 5.12, 8.39 and 13.51 t ha1, respectively and harvest index (37.85%) at harvest while without phosphorus obtained the lower results on the above. In case of Sulphur, all the traits were significant except plant height at 55, 85 DAT and at harvest, filled grains panicle1 and 1000-grain weight whereas 20 kg S ha1 obtained the tallest plant (109.40 cm) at harvest and maximum tillers hill1 (16.28) at 85 DAT. The maximum effective tillers hill1 (12.12), longest panicle (21.35), higher weight of grain, straw and biological yield 4.75, 8.08 and 12.82 t ha1, respectively and harvest index (36.90%) were taken in 20 kg S ha1 at harvest. It was also observed the minimum non effective tillers hill1 (2.83) and unfilled grains panicle1 (12.04) whereas all the Sulphur levels were produced statistically similar filled grains panicle1 and 1000-grain weight at harvest due to non significant variation. The present findings obviously recommended that 40 kg P ha1 or 20 kg S ha1 singly or their interactions would be optimum level for getting the higher production of BRRI dhan 57.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22137 J. Environ. Sci. & Natural Resources, 7(1): 7-11 2014